The archaeology of medieval Islamic frontiers from the Mediterranean to the Caspian Sea - Eger, A. Asa (University Press of Colorado, 2019)
"Different areas of the Islamic polity previously understood as "minor frontiers" were in fact of substantial importance to ancient state formation. Exploring different concepts of "border" in areas whose importance previously went unrecognized, including Maghreb, the Mediterranean, Egypt, Nubia, and the Caucasus through archaeological and documentary evidence"--Provided by publisher
Keywords: Geschichte 700-1500; Grenze; Islam; Islamic Empire / Antiquities; Islamic Empire / Boundaries; Borderlands / Islamic Empire; Antiquities; Borderlands; Boundaries; Islamic Empire